Selective CO2 and H-2 adsorption in a chiral magnesium-based metal organic framework (Mg-MOF) with open metal sites - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Journal of Materials Chemistry, 2010)
A rare porous magnesium-based metal-organic framework, Mg-MOF-1 [Mg(3,5-PDC)(H2O)], was synthesized solvothermally in DMF. Structural determination by X-ray single-crystal diffraction technique reveals that this chiral MOF (space group P6(1)22) is constructed by helical assembly of Mg2+ ions with achiral 3,5-pyridine dicarboxylates and coordinating water molecules, to form a three-dimensional framework with parallel hexagonal channels. The structural detail of its 0D analogue Mg-MOF-2 [Mg(2,4-PDC)(H2O)(3)] has been discussed to show how subtle variation in the ligand architecture changes the resulting structure from 0D to 3D. Mg-MOF-1 remains robust and porous upon evacuation of the coordinating water molecules. This is the first report of a chiral hexagonal Mg-MOF synthesized from an achiral organic building unit. Open Mg metal sites show selective hydrogen (H-2) adsorption (ca. 0.8 wt% at 77 K) and carbon dioxide (CO2) uptake (ca. 0.7 mmol g(-1) at 298 K) over nitrogen at 1 atm. Ab initio quantum chemical calculation of adsorption energies and possible adsorption sites of hydrogen molecules are also reported.

Structure and gas sorption behavior of a new three dimensional porous magnesium formate - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Inorganic Chemistry, 2011)
A new three-dimensional magnesium formate polymorph, namely, gamma-[Mg-3(O2CH)(6)] has been synthesized via in situ formate anion generation method. gamma-Mg-formate crystallizes in space group Pbcn, and structural determination by X-ray single crystal diffraction reveals a three-dimensional network of Mg2+ linked by formate anions. All formate anions possess similar binding mode to the metal center with one oxygen of a particular formate anion binds to one metal center (mu(1) oxygen) and other oxygen binds to two metal centers (mu(2) oxygen). N-2 adsorption studies indicate that the framework displays permanent porosity. The specific surface area of gamma-Mg-formate (BET, 120 m(2) gm(-1)) is lower than the alpha- polymorph (BET, 150 m(2) gm(-1)). However, the initial hydrogen uptake of gamma-Mg-formate reached almost 1.0 wt % when the adsorbate pressure approached 760 Torr at 77 K. This is higher than the hydrogen uptake of alpha-Mg-formate (0.6 wt %). gamma-Mg-formate, shows a moderate affinity and capacity for CO2 (3.4 angstrom kinetic diameter) at 298 K. The CO2 uptake at 760 Torr is 2.01 mmol gm(-1)(47.0 cc gm(-1)). Although this CO2 uptake is somewhat modest, it compares well with the CO2 uptake of several Mg-MOFs and ZIFs reported in the literature.

Correlation between coordinated water content and proton conductivity in Ca-BTC-based metal-organic frameworks - Mallick, Arijit; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
Proton conductivity of five Ca-based MOFs which depends on the amount of water molecules coordinated to the Ca-centres has been reported. These MOFs show high temperature proton conductivity due to the strong hydrogen bonding between the lattice and coordinated water molecules.

Crystal structure of (2S, 4R)-2-benzyl 1-tert-butyl 4-(tosyloxy)pyrrolidine-1,2-dicarboxylate, C24H29NO7S - Ghosh, Munmun; Mallick, Arijit; Diaz, David Diaz (Zeitschrift Fur Kristallographie-New Crystal Structures, 2012)
{C24H29NO7S, triclinic, P1 (no. 1)

Fine-tuning the balance between crystallization and gelation and enhancement of CO2 uptake on functionalized calcium based MOFs and metallogels - Mallick, Arijit; Schoen, Eva-Maria; Panda, Tamas; Sreenivas, K.; Diaz, David Diaz; Banerjee, Rahul (Journal of Materials Chemistry, 2012)
The synthesis, structure, gas adsorption and catalytic properties of a new 3D porous, crystalline metal-organic framework (Ca-5TIA-MOF) as well as stable viscoelastic metallogels (Ca-5TIA-Gel) are reported. Remarkably, the preparation of both types of materials can be carried out starting from the same organic ligand (i.e. 5-(1,2,4-triazoleyl) isophthalic acid (5TIA)), divalent metal ion (i.e. Ca(II)) and organic solvent (i.e. DMF). In this particular case, the presence of water in the solvent system favors the formation of a crystalline MOF, whereas a pure organic solvent induces gelation. The characterization of the materials was carried out using a series of techniques including XRD, FT-IR, TGA, TEM, SEM, SAXS and dynamic rheology. Experimental PXRD peaks of both Ca-5TIA-xerogel and Ca-5TIA-MOF matched reasonably well with simulated PXRD, suggesting the presence of, at least, some common structural elements in the 3D networks of both xerogel and crystalline phases. Moreover, the nature of the metal counteranion was found to have a critical influence on the gelation phenomenon. To the best of our knowledge, this report describes unprecedented Ca-based LMW-metallogels, as well as the first porous Ca-based MOF, which shows adsorption capacity for CO2 at 1 atm pressure. Interestingly, Ca-5TIA-xerogel presented 20% higher CO2-uptake than the crystalline Ca-5TIA-MOF at 1 atm and 298 K. Both Ca-5TIA-MOF and Ca-5TIA-Gel also displayed a modest catalytic activity towards the hydrosilylation of benzaldehyde, with slightly better performance for the gel phase material.

Efficient and stereoselective nitration of mono- and disubstituted olefins with AgNO2 and TEMPO - Maity, Soham; Manna, Srimanta; Rana, Sujoy; Naveen, Togati; Mallick, Arijit; Maiti, Debabrata (Journal of the American Chemical Society, 2013)
Nitroolefin is a common and versatile reagent. Its synthesis from olefin is generally limited by the formation of mixture of cis and trans compounds. Here we report that silver nitrite (AgNO2) along with TEMPO can promote the regio- and stereoselective nitration of a broad range of olefins. This work discloses a new and efficient approach wherein starting from olefin, nitroalkane radical formation and subsequent transformations lead to the desired nitroolefin in a stereoselective manner.

Electron rich porous extended framework as a heterogeneous catalyst for Diels-Alder reactions - Gole, Bappaditya; Bar, Arun Kumar; Mallick, Arijit; Banerjee, Rahul; Mukherjee, Partha Sarathi (Chemical Communications, 2013)
An electron rich porous metal-organic framework (MOF) has been synthesized, which acts as an effective heterogeneous catalyst for Diels-Alder reactions through encapsulation of the reactants in confined nano-channels of the framework.

Hydrolytic conversion of a metal-organic polyhedron into a metal-organic framework - Mallick, Arijit; Garai, Bikash; Diaz, David Diaz; Banerjee, Rahul (Angewandte Chemie-International Edition, 2013)
Keywords: cage compounds; crystal engineering; hydrophobic effect; metal-organic frameworks; Self-assembly

Synthesis, structure, and H-2/CO2 adsorption in a three-dimensional 4-connected triorganotin coordination polymer with a sqc topology - Chandrasekhar, Vadapalli; Mohapatra, Chandrajeet; Banerjee, Rahul; Mallick, Arijit (Inorganic Chemistry, 2013)
A 4-connected triorganotin 3D coordination polymer in a sqc topology has been shown to possess 1D microchannels along its crystallographic a axis. This main-group-element-containing framework structure shows selective gas adsorption, preferring CO2 and H-2 over N-2.

Crystalline metal-organic frameworks (MOFs): synthesis, structure and function - Dey, Chandan; Kundu, Tanay; Biswal, Bishnu P.; Mallick, Arijit; Banerjee, Rahul (Acta Crystallographica Section B-Structural Science, 2014)
Metal-organic frameworks (MOFs) are a class of hybrid network supramolecular solid materials comprised of organized organic linkers and metal cations. They can display enormously high surface areas with tunable pore size and functionality, and can be used as hosts for a range of guest molecules. Since their discovery, MOFs have experienced widespread exploration for their applications in gas storage, drug delivery and sensing. This article covers general and modern synthetic strategies to prepare MOFs, and discusses their structural diversity and properties with respect to application perspectives.

Gold(I)/chiral brønsted acid catalyzed enantioselective hydroamination-hydroarylation of alkynes: effect of remote hydroxyl group in the reactivity and enantioselectivity - Shinde, Valmik S.; Mane, Manoj V.; Vanka, Kumar; Mallick, Arijit; Patil, Nitin T. (Chemistry - A European Journal, 2015)

Hollow tubular porous covalent organic framework (COF) nanostructures - Pachfule, Pradip; Kandmabeth, Sharath; Mallick, Arijit; Banerjee, Rahul (Chemical Communications, 2015)
Hollow and tubular TpPa-COF structures have been synthesized by template-assisted replication of nanometer sized ZnO-nanorods. The hollow structures composed of microporous TpPa shells have high periodicity, moderate porosity, chemical stability and capsule shaped morphology as revealed by X-ray diffraction, porosity measurements, and SEM and TEM analyses.

Solid state organic amine detection in a photochromic porous metal organic framework - Mallick, Arijit; Garai, Bikash; Addicoat, Matthew A.; Petkov, Petko St.; Heine, Thomas; Banerjee, Rahul (Chemical Science, 2015)
A new Mg(II) based photochromic porous metal-organic framework (MOF) has been synthesized bearing naphthalenediimide (NDI) chromophoric unit. This MOF (Mg-NDI) shows instant and reversible solvatochromic behavior in presence of solvents with different polarity. Mg-NDI also exhibits fast and reversible photochromism via radical formation. Due to the presence of electron deficient NDI moiety, this MOF exhibits selective organic amine (electron rich) sensing in solid state. The organic amine detection has been confirmed by photoluminescence quenching experiment and visual color change.

Photochromic metal-organic frameworks for inkless and erasable printing - Garai, Bikash; Mallick, Arijit; Banerjee, Rahul (Chemical Science, 2016)
Inkless and erasable printing is the key solution towards a more sustainable paper industry, in terms of reducing paper wastages and the associated environmental hazards from waste paper processing. However, only a few cases have been reported in the literature where inkless printing has been tested in some practical systems. In an attempt to address this solution, we used photochromic metal-organic frameworks (MOFs) and tested their capability as inkless and erasable printing media. The printing was performed using sunlight as the light source on MOF-coated papers. The resulting printing had good resolution and stability, and was capable of being read both by the human eye and smart electronic devices; furthermore, the paper could be reused for several cycles without any significant loss in intensity. Interestingly, different coloured printing with a similar efficiency was achieved by varying the structure of the MOF.

Self-exfoliated metal-organic nanosheets through hydrolytic unfolding of metal-organic polyhedra - Garai, Bikash; Mallick, Arijit; Das, Anuja; Mukherjee, Rabibrata; Banerjee, Rahul (Chemistry-A European Journal, 2016)
Few-layers thick metal-organic nanosheets have been synthesized using water-assisted solid-state transformation through a combined top-down and bottom-up approach. The metal-organic polyhedra (MOPs) convert into metal-organic frameworks (MOFs) which subsequently selfexfoliate into few-layered metal-organic nanosheets. These MOP crystals experience a hydrophobicity gradient with the inner surface during contact with water because of the existence of hydrophobic spikes on their outer surface. When the amount of water available for interaction is higher, the resultant layers are not stacked to form bulk materials; instead few-layered nanosheets with high uniformity were obtained in high yield. The phenomenon has resulted high yield production of uniformly distributed layered metal-organic nanosheets from three different MOPs, showing its general adaptability.